Tame or domesticate? The problem of islamization of Europe on the example of Spain = Poskramiać czy oswajać? Problem islamizacji Europy na przykładzie Hiszpanii - Masłowska, Martyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article discusses the problem of islamization of Europe based on the Spanish experience. The aim was to show the aspirations of the Muslim community in Spain to implement Sharia law. Strict rituals and rules of Islam are imposed on all believers and affect every aspect of their lives. This pro-cess is becoming more visible in Spain, due to the alarming information on the demographic growth of the Muslim population, and consequently making community`s efforts to achieve tolerance and official recognition of this religion. Qis necessitates the development of new strategies in Spain and political action.
Keywords: islam; muslims; Spain; religion; muzułmanie; Hiszpania; religia